Updated PSO optimised fuzzy-PI controlled buck type multi-phase inverter-based PMSM drive with an over-current protection scheme - Sain C.; Banerjee A.; Biswas P.K.; Babu T.S.; Dragicevic T. (Institution of Engineering and Technology, 2023)
DC-DC converters; Electric inverters; Fuzzy logic; Light electric vehicles; Light weight vehicles; Particle swarm optimization (PSO); Permanent magnets; Pulse width modulation; Synchronous motors; Traction motors; Two term control systems; Voltage control; Water craft; Current control strategy; Current source inverter; Fuzzy logic controllers; MATLAB /simulink; Operating condition; Permanent magnet synchronous motor drives; Proportional integral; Voltage source inverter; Electric machine control